The Gastroenterologist’s Guide to Preventive Management of Compensated Cirrhosis - Shetty, Akshay (Gastroenterol Hepatol (N Y), 2019)
Despite advances in medical care, the prevalence and mortality associated with cirrhosis continue to rise. The majority of medical care and physician efforts are devoted to the management of decompensated cirrhosis and its complications of gastrointestinal hemorrhage, hepatic encephalopathy, and ascites; however, limited efforts are placed on the medical management of compensated cirrhosis. Patients with compensated cirrhosis carry a higher survival rate, and, when diagnosed early, may be screened for future decompensation. When possible, these patients can be treated for their underlying disease to prevent disease progression and avoid the need for liver transplantation. This article reviews the importance of early diagnosis, outpatient management of compensated cirrhosis, early screening for potential decompensation, and patient education.